Trends in Incarceration and Recidivism in Mauritius a Raising the Alarm (Global Journal of Human-Social Science, 2011)
Keywords Recidivism Re-integration of ex-detainees ExpenditureCorrectional and incarceration policies for crime and deviance have as consequences the following Retribution which is an expression of society s moral outrage Deterrence which argues that punishment for offenders should be sure speedy commensurate with crime and sufficiently conspicuous to deter others from committing crimes Incapacitation that is protecting the public from lawbreakers or habitual criminals by segregating them behind prison walls and finally Rehabilitation whereby the theoretical paradigm is that criminals are partly or entirely victims of social circumstances beyond their control and that society owes them a comprehensive treatment in the form of rehabilitation Rehabilitative measures could be deemed as an attempt to equip them with the necessary skills in order to try to re-integrate society and consequently prevent recidivism Recidivism comprises a common theme which is generally used for describing repetitious criminal activity and a recidivist offender is an individual who engages in such activity Each year a large number of people are released from prisons in Mauritius The obstacles to successful re-integration are numerous such as the challenge of finding stable employment There have been no or few rigorous studies of re-entry models and there is a pressing need for more definitive evidence of what works in order to prevent the gangrene of recidivism and degrading law and order to permeate our society This paper reviews theories present facts and figures and initiatives describing some planned or ongoing endeavours and proposes some ideas for future efforts in order to decrease recidivism in Mauritius
Keywords: Recidivism; Re-integration of ex-detainees; Expenditure